Penerapan Model Regresi Linier dalam Prediksi Harga Mobil Bekas di India dan Visualisasi dengan Menggunakan Power BI - Muhammad Devanda Hendra Kusuma; Syarif Hidayat (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The growing message of the global automotive industry has led to an increase in used car sales, especially in unique consumer behavior markets like India. Pricing used cars presents challenges due to inconsistent factors such as mileage and age. This study aims to contribute to the understanding of the used car market in India and provide valuable information for business owners and industry players to make informed decisions. The results show that linear regression is accurate and forms a multiple linear regression model y = -1998.21+ 9.9 X1+ 1.22 X2+ 1.3 X3 -8.07 X4+ 1.83 5889267114422 and UMK 49.222702208411334. Apart from that, in the testing process the model built had an accuracy level of 71.09%. This research aims to predict used car prices by considering influencing factors, and the results will be presented visually to provide business owners with more interactive information.